2010
DOI: 10.3354/dao02200
|View full text |Cite
|
Sign up to set email alerts
|

Anuran susceptibilities to ranaviruses: role of species identity, exposure route, and a novel virus isolate

Abstract: Ranaviruses are responsible for widespread amphibian die-offs, particularly with larval anurans. To understand the factors that may be contributing to the emergence of ranaviruses, we conducted 3 experiments that exposed 3 species of larval anurans to either endemic frog virus 3 (FV3) or an FV3-like isolate from a ranaculture facility. Our goals were to (1) determine the susceptibility of each species to each virus, (2) determine whether direct ingestion of virions or exposure to virions in a water bath were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
136
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(140 citation statements)
references
References 59 publications
4
136
0
Order By: Relevance
“…Regarding ST 50 , mortality of Cope's grey tree frog tadpoles [Hyla chrysoscelis, family Hylidae, found in the south-eastern United States (Dodd, 2013)] exposed to water containing FV3 began 12 days p.i. and reached 66 % (Hoverman et al, 2010), whereas mortality of tiger salamander tadpoles [Ambystoma tigrinum, family Ambysomatidae, found in southern Canada, the continental USA and north-eastern Mexico (Duellman & Trueb, 1994)] also exposed to water containing FV3 began just under 20 days p.i. and reached 91 % (Brunner et al, 2005).…”
Section: Fv3 Ranavirus Multidose Trial Infection Of Wood Frogsmentioning
confidence: 99%
See 4 more Smart Citations
“…Regarding ST 50 , mortality of Cope's grey tree frog tadpoles [Hyla chrysoscelis, family Hylidae, found in the south-eastern United States (Dodd, 2013)] exposed to water containing FV3 began 12 days p.i. and reached 66 % (Hoverman et al, 2010), whereas mortality of tiger salamander tadpoles [Ambystoma tigrinum, family Ambysomatidae, found in southern Canada, the continental USA and north-eastern Mexico (Duellman & Trueb, 1994)] also exposed to water containing FV3 began just under 20 days p.i. and reached 91 % (Brunner et al, 2005).…”
Section: Fv3 Ranavirus Multidose Trial Infection Of Wood Frogsmentioning
confidence: 99%
“…ml 21 : a dose very close to the concentration of FV3 that caused 66 % mortalities in Cope's grey tree frogs. Hoverman et al (2010), by using a consistent methodology, demonstrated that tadpoles of three different species [pickerel frog, Rana (Lithobates) palustris, Cope's grey tree frog, and eastern narrow-mouthed toad, Gastrophryne carolinensis] are not equally susceptible to mortality when exposed to FV3. The authors also concluded that oral inoculation of a known dose of FV3 (10 6 p.f.u.)…”
Section: Fv3 Ranavirus Multidose Trial Infection Of Wood Frogsmentioning
confidence: 99%
See 3 more Smart Citations